Innovative Marketing Technology in the Food and Beverage Industry in Malaysia - Amiruddin AHAMAT; Muhamad Sham SHAHKAT ALI; Muhamad Afnan AZAMI (Communications of International Proceedings, 2021)
Nowadays, Food and Beverage (F&B) sector are more focused on using marketing technology in introducing their products and enhancing their company's image in the market. However, consumer adoption technology of product or service continues to be a challenge for the marketer in the market. This is because consumers are more attracted in using new technology to get the information and buy the product through online marketing. This main purpose of this research is to examine the use of innovative marketing technology in MAMEE-Double Decker (M) Bhd., Malaysia. In this case, the competitive environment has driven MAMEE-Double Decker (M) Sdn. Bhd. to adapt an aggressive promotional strategy to gain market share. This research also aims to investigate the factors influencing the adaption of Innovative Marketing Technology and its impact on the F&B sector in Malaysia. This study adopts qualitative methodology through in-depth interviews with the selected participants, hence providing insights and understanding of the complex phenomena in the company. The outcome of this study demonstrates that effectiveness of innovative marketing technology within business practices ensures the company remains sustainable and competitive. Future study, employing longitudinal approach extending to other small and medium enterprises would be enriching the marketing technology context. This study is important as it can be used as a guide for businesses in the Food and Beverage sector as nowadays innovation is one of the important solutions for companies to remain and succeed in increasingly competitive markets in Malaysia.
Keywords: Innovative Marketing; Technology; Case Study; Consumer Acceptance.